Income risk and consumption inequality: A simulation study - Richard W. Blundell; Hamish Low; Ian Preston (Institute for Fiscal Studies (IFS), 2004)
This paper assesses the accuracy of decomposing income risk into permanent and transitory components using income and consumption data. We develop a specific approximation to the optimal consumption growth rule and use Monte Carlo evidence to show that this approximation can provide a robust method for decomposing income risk. The availability of asset data enables the use of a more accurate approximation allowing for partial self-insurance against permanent shocks. We show that the use of data on median asset holdings corrects much of the error in the simple approximation which assumes no self-insurance against permanent shocks.
Keywords: C30; D52; D91; 330; income risk; inequality; approximation methods; consumption; Einkommen; Risiko; Einkommensverteilung; Simulation; Monte-Carlo-Methode